Introduction - Lund, Jacob (The Nordic Journal of Aesthetics, 2017)
Rather than addressing an overall theme the present issue of The Nordic Journal of Aesthetics – in a new design by Studio Claus Due – presents independent articles of different scopes and perspectives.